The Utilization of Candlenut Shell-Based Activated Charcoal as the Electrode of Capacitive Deionization (CDI) for Seawater Desalination - Anas, Muhammad; Napirah, Mardiana; Ilmawati, Wa Ode Sitti; Husein; Takda, Amiruddin; Herawati, Like; Ima; Sari, Karmila (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Activated carbon or activated charcoal is one of the best materials that can be used as a constituent of CDI electrodes, not only because of its various advantageous properties but also because it can be sourced abundantly from plant waste. This research aims to determine the effect of the thickness of the candlenut shell activated charcoal electrode and the particle size of the activated carbon used on the capacitive deionization (CDI) performance in seawater desalination. Candlenut shell-based activated charcoal is obtained in three stages, namely preparation, carbonization, and activation. The carbonization stage was done by using a pyrolysis reactor at a temperature of 400°C for 8 hours. The activation was done with the activator of H3PO4 67%. The variation of thickness was 6 mm, 8 mm, 10 mm, and 15 mm while the variation of particle size was 60 mesh, 80 mesh, 100 mesh, and 200 mesh. The results showed that the higher capacitance was obtained with the thinner electrodes, where the best value was the thinnest electrode, 6 mm, which produced the highest capacitance, 122.96 nF. For the desalination of seawater, it is shown that the finest particle/smallest particle size will result in the best desalination performance, where 200 mesh particle size will result in the decrease of salinity from 34% to 4%. That is 88.23% decrease in salinity. Therefore, the using of candlenut shell-based activated carbon as the electrode in CDI is proven to be able to obtain good performance in seawater desalination.